“Proceso de Reconocimiento de Impuestos Diferidos en la Empresa TUBASEC c.a. de la Ciudad de Riobamba, durante el año 2014, para establecer una metodología de contabilización y medición. - Londo Villafuerte, Paola Alexandra (2016)
SUMMARY: This research established a methodology for accounting and measurement to be followed by the recognition of deferred taxes. Tubasec C.A., was chosen because they use International Financial Reporting Standards which recognizes deferred tax. Tubasec C.A., needs this tool implementation as a guide for a better usage, as well as, the demand of accounting rules and law application, in order to employees and the General Accountant be trained to recognize this tax. This practice was developed setting the general parameters for the methodology application that would be viable and to ensure its efficiency and effectiveness in determining their accounting and tax obligations, in order to measure the information reliability. Meanwhile the implementation of International Financial Reporting Standards IFRS, at Tubasec C.A., the financial interpretation of statements are of greater understanding, quality and transparency, by this means generating a better decision making for the company's board. Tubasec C.A., for bookkeeping uses the deferred taxes method, because it allows to correct errors presented in traditional accounting processes, in order to associate the time of admission to the related spending, so that the differences between tax and accounting rules create impacted tax purposes in diverse periods.